Molecular delimitation and taxonomic revision of the wimple piranhaCatoprion(Characiformes: Serrasalmidae) with the description of a new species - Bonani Mateussi, Nadayca T. [UNESP]; Melo, Bruno F. [UNESP]; Oliveira, Claudio [UNESP] (Wiley-Blackwell, 2020)
A taxonomic revision of wimple piranhas of the genusCatoprionis performed in combination with a molecular analysis using mtDNA. Molecular phylogenetic analyses of 49 specimens using genetic distances, conventional likelihood and four delimitation methods yielded two distinct lineages ofCatoprion, with the morphological analyses of 198 specimens ofCatoprioncorroborating the molecular results. We provide a redescription ofCatoprion mento, from the Paraguay, Orinoco, and tributaries of western Amazon basin, keepingMylesinus macropterusas a junior synonym ofC. mento, and the description ofCatoprion absconditusn. sp., from the Amazon and Essequibo basins.C. absconditusn. sp. differs fromC. mentoby the presence of 86-94 perforated scales in the lateral line (vs.65-86 scales) and the presence of 35-40 circumpeduncular scales (vs.29-34 scales). The distribution ofC. mentofollows the Amazonas-Paraguay-Orinoco lowlands, whereasC. absconditusfollows the eastern Amazon biogeographic pattern.
Keywords: biodiversity; DNA barcoding; Neotropical region; systematics; Teleostei